Evaluation of decision making processes of a venture capital firm from the CEE region - Jiránek, Pavel (2018)
The Master’s thesis Evaluation of Decision Making Process of a Venture Capital Firm from the CEE Region examines various elements of the decision-making process of one particular venture capital firm. Through the Mixed Method of research, this study aims to (i) identify the key decisive factors, that are being considered during the process, (ii) to evaluate various sources of deal flow and (iii) to offer a deeper understanding of the reasoning of investment officers, when performing certain decisions. The empirical part is divided into two parts;In the first part, a quantitative analysis is performed. As such, it offers fundamental statistical findings as well as it allows for the evaluation of the key decisive factors. Moreover, through more advanced statistical methods, the significance of various sources of deal flow is examined.In the second part, the qualitative analysis offers an unusual insight into the thought- process of the investment officers as well as real examples of wording used, when making the final decision. Moreover, 9 individual use cases of investment proposals are presented and analyzed.By combining the two kinds of analyses, this Thesis brings value not only to the analyzed firm but also to any aspiring start-up, which might seek venture capital funding in the future.